2018
DOI: 10.2147/tcrm.s171563
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination ability of the endotracheal tube location using real-time palpation during intubation using an endotracheal tube with a preloaded stylet

Abstract: PurposePalpation during intubation could be used as an ancillary method of providing real-time information of the endotracheal tube (ETT) placement before manual ventilation. This study aimed to evaluate the ability to discriminate the ETT location using a modified real-time palpation method with a preloaded stylet during intubation.Patients and methodsThe examiner performing the real-time palpation method placed three fingers on the lateral sides of the trachea between the sternal notch and the thyroid cartil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
(38 reference statements)
0
4
1
Order By: Relevance
“…The reported incidence of esophageal intubation among patients without obesity varies from 1.25% to 8.6%, which is markedly lower than the rate obtained for the obese patients in our study (13.8%) . This finding may be related to the anatomic changes in the upper airway of patients with obesity.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The reported incidence of esophageal intubation among patients without obesity varies from 1.25% to 8.6%, which is markedly lower than the rate obtained for the obese patients in our study (13.8%) . This finding may be related to the anatomic changes in the upper airway of patients with obesity.…”
Section: Discussioncontrasting
confidence: 85%
“…19 The reported incidence of esophageal intubation among patients without obesity varies from 1.25% to 8.6%, which is markedly lower than the rate obtained for the obese patients in our study (13.8%). [20][21][22] This finding may be related to the anatomic changes in the upper airway of patients with obesity. These changes include oropharyngeal crowding, narrowing of the upper airway, macroglossia, retrognathia, a thick neck, a reduced mandibular length, an inferiorly positioned hyoid bone, and a retroposition of the maxilla.…”
Section: Discussionmentioning
confidence: 87%
“…Of these, we excluded 31, and following a detailed assessment included 49 studies (29 observational, 18 randomised controlled trials, 2 studies where the design was not reported) involving 10,654 participants in the final review (Fig. 1) [3, 18–65]. Overall, the median number of participants per study was 67.5.…”
Section: Resultsmentioning
confidence: 99%
“…We found only one study reporting on chest movement, in a non‐human model [58]. Twenty‐two studies used a form of capnography as the reference standard [23, 27, 29, 30, 33, 34, 36, 37, 42, 47, 50‐57, 64–66] and three used bronchoscopy [20, 26, 39]. Ten studies, all conducted before 1996, relied solely on direct vision at the time of laryngoscopy or a combination of clinical signs alone [18, 22, 25, 28, 32, 40, 41, 44, 60, 63], whereas another 10 studies did not clearly report the reference standard [18, 19, 21, 31, 35, 46, 60–63].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation